A layered porous adsorption material, preparation method and electric adsorption device
By forming a layered porous structure on the adsorption material and using electro-adsorption technology, the problems of low adsorption capacity, slow rate and non-selectivity in the treatment of high-concentration nitrate waste liquid are solved, and efficient, economical and environmentally friendly nitrate ion adsorption effect is achieved.
Patent Information
- Application Number
- CN202510272506.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems such as low adsorption capacity, slow adsorption rate and ion-free selectivity when treating high-concentration nitrate waste liquid, resulting in high processing efficiency and cost, and the risk of secondary pollution.
A layered porous adsorption material is used to form a chemical etching effect through the reaction of silica and polytetrafluoroethylene to form a layered porous structure on the surface of the material. Combined with electrosorption technology, an electrostatic field formed on the electrode surface is used to achieve efficient adsorption of nitrate ions.
The adsorption capacity and adsorption speed are greatly improved, and the high selective adsorption of nitrate ions is achieved, which reduces operating costs and energy consumption, and can resourcefully utilize the desorbed concentrate.
Smart Images

Figure CN119771355A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sewage treatment, and in particular relates to a layered porous adsorption material, a preparation method and an electric adsorption device. Background Art
[0002] Many industrial production processes will produce a large amount of high-concentration nitrate waste liquid, such as the pharmaceutical, chemical, electronics, food processing, printing and dyeing industries. Taking the pharmaceutical industry as an example, during the process of drug synthesis and fermentation, wastewater containing high concentrations of organic nitrogen will be produced; and the chemical industry will also produce wastewater containing a large amount of nitrogen compounds during the production process. For example, in the production process of nitrogen fertilizer (ammonium nitrate), wastewater containing high concentrations of nitrate will be discharged; and in some chemical synthesis reactions, nitric acid may be used as an oxidant or catalyst, resulting in high concentrations of nitrate ions in the wastewater. The rapid development of the chemical and pharmaceutical industries has led to an increasing amount of high-concentration nitrate waste liquid, and the potential threat to the environment is becoming increasingly serious.
[0003] Traditional methods for treating high-concentration nitrate wastewater, such as biological methods and chemical methods, have certain limitations in terms of treatment effect, operating cost, and operation management. Biological methods for treating high-concentration nitrate wastewater are sensitive to environmental conditions. Changes in temperature will greatly affect the activity of microorganisms. The metabolic rate will decrease at low temperatures, and the treatment effect will be greatly reduced; while high temperatures may inactivate microorganisms. The pH value must also be within a specific range, otherwise it will inhibit microbial growth and metabolism. At the same time, the control of dissolved oxygen is also crucial, and insufficient oxygen will limit microbial activity. In addition, the biological method has a long treatment cycle, the growth and reproduction of microorganisms are slow, and it often takes several days or even weeks to completely remove nitrates. It has poor adaptability to high-concentration wastewater, and high concentrations of nitrates will have toxic inhibition on microorganisms, affecting the normal operation of the system. The chemical method has a high treatment cost. On the one hand, a large amount of chemical agents, such as oxidants and reductants, are required, and the cost of agents accounts for a large proportion. On the other hand, chemical treatment requires special equipment, with large investments and high maintenance costs. The easy generation of secondary pollution is also a prominent problem of chemical methods. A large amount of sludge will be generated during the treatment process, which contains unreacted agents and reaction products. If it is not handled properly, it will cause secondary pollution. At the same time, some chemical treatment methods may produce toxic byproducts. In addition, chemical methods are complex to operate and manage, require precise control of reaction conditions, have high requirements for operators, and have certain safety risks. Some chemical agents are dangerous, and improper operation may cause leaks, explosions and other accidents. Therefore, the industry urgently needs to develop more efficient, economical and environmentally friendly treatment technologies and processes.
[0004] Electrosorption technology uses the charged electrode surface to adsorb charged ions in water, so that the substances in the water are concentrated and enriched on the electrode surface, thereby realizing efficient and energy-saving low-salt or medium-salt water desalination technology. The electrosorption process is divided into two parts: adsorption process and desorption process. When the treated water passes through the porous electrode, it will be affected by the electric field force applied by the system. When the charged charge on the electrode enters the solution, the ions in the solution are redistributed and arranged; at the same time, under the action of Coulomb force, the interface between the charged electrode and the solution is occupied by counterions, and the change of the residual charge on the interface will cause the change of the interface double-layer potential difference, thereby forming a dense double layer at the interface between the electrode and the electrolyte. The anions and cations in the solution gradually migrate to the electrode plates with opposite polarity, and the ions are adsorbed on the surface of the material to achieve the purpose of removing pollutants. As the reaction proceeds, the ions adsorbed on the electrode surface reach saturation, and the adsorbent material needs to be desorbed and regenerated. Generally, desorption is carried out by reversing the polarity or short-circuiting, so that the ions adsorbed on the surface of the material are released into the solution through the repulsive effect of the electric field, and finally concentrated water is generated and discharged to achieve desorption. Although electrosorption technology has advantages such as energy saving and no secondary pollution, the following technical obstacles still exist at this stage: ① Low adsorption capacity. Although some electrode materials have a large specific surface area and can theoretically provide a higher adsorption capacity, in practical applications, the accessibility and storage capacity of ions inside the material are limited due to factors such as the structure of the material itself and the pore size distribution. The microporous structure of some carbon material electrodes may make it difficult for ions to enter due to the small pore size, and the internal adsorption space cannot be fully utilized, thereby limiting the improvement of adsorption capacity. In addition, in actual wastewater systems, there are a variety of ions and substances, which will compete with each other for the adsorption sites on the electrode surface, resulting in the adsorption capacity of the target ions being affected. For example, in industrial wastewater containing a variety of metal ions and anions, the presence of other ions may occupy some adsorption sites and reduce the adsorption of specific nitrate ions.
[0005] ② Slow adsorption rate. During the electrosorption process, ions need to migrate from the main body of the solution to the electrode surface and enter the double layer. The mass transfer rate of this process is affected by many factors, and the pore structure of the electrode is one of the important determining factors. If the mass transfer rate is slow, it will limit the overall adsorption rate. In actual application scenarios, especially for high-concentration, large-flow wastewater treatment, mass transfer limitations may become a bottleneck for improving treatment efficiency.
[0006] ③ No ion selectivity. Different ions have different characteristics such as charge number, ion radius, hydration energy, etc., which will affect their migration speed in the electric field and adsorption capacity on the electrode surface. For some ions with similar properties to nitrate ions, electrosorption technology may be difficult to achieve efficient selective adsorption, resulting in unsatisfactory separation effect. Summary of the invention
[0007] In view of this, the present invention aims to provide a layered porous adsorption material, a preparation method and an electric adsorption device to solve at least one technical problem in the background technology.
[0008] To achieve the above object, the technical solution of the present invention is achieved as follows: A method for preparing a layered porous adsorption material comprises the following steps: firstly mixing a chitosan solution and SiO2, then adding polytetrafluoroethylene and stirring to form a milky white solution; The milky white solution is freeze-dried to obtain a solid mixture, the solid mixture is heat-treated in an inert gas, cooled, washed with deionized water, and dried to obtain a layered porous adsorption material.
[0009] The role of polytetrafluoroethylene is to react with silicon dioxide in the subsequent carbonization process, so that the silicon dioxide that originally occupied the position forms a vacancy. At the same time, the reaction produces a large amount of gas, which promotes the further expansion of the pores. The reaction equation is as follows: (1); (2); (3); Therefore, the role of polytetrafluoroethylene is to participate in the material synthesis reaction and promote the matrix to form a layered porous structure.
[0010] Furthermore, the solvent in the chitosan solution in step A1 is glacial acetic acid.
[0011] Furthermore, the mass ratio of chitosan solution, SiO2 and polytetrafluoroethylene is 1:4:2-4.
[0012] And / or, SiO2 is colloidal SiO2.
[0013] Furthermore, the inert gas is nitrogen.
[0014] And / or, the heat treatment temperature is 890-910°C and the heating rate is 8-12°C / min.
[0015] And / or, the heat treatment time is 3-5h.
[0016] And / or, the drying temperature is 90-110°C, and the drying time is 1.8-2.2h.
[0017] The above-mentioned method for preparing a layered porous adsorption material prepares a layered porous adsorption material.
[0018] Hierarchically porous carbon (HPC) is a carbon material with different pore sizes and structures. The hierarchically porous adsorption material of the present invention is also named HPC.
[0019] The HPC anode is an anode prepared using a hierarchical porous adsorption material; The HPC cathode is a cathode prepared using a hierarchical porous adsorption material; Cationic HPC powder is an anode powder prepared using a layered porous adsorption material; Anionic HPC powder is a cathode powder prepared using a layered porous adsorption material.
[0020] An electrosorption device, comprising an HPC anode and an HPC cathode prepared using the layered porous adsorption material prepared above; The HPC anode and the HPC cathode are placed symmetrically, the interval between the HPC anode and the HPC cathode is 4-6 mm, plastic fibers are filled between the HPC anode and the HPC cathode, wires are led out from the HPC anode and the HPC cathode respectively, and the HPC anode and the HPC cathode are connected to the positive and negative electrodes of the power supply respectively through the wires to obtain an electric adsorption device.
[0021] The voltage of the electric adsorption device connected to the power supply is less than 1.2V.
[0022] In this application, plastic fibers are filled between the HPC anode and the HPC cathode to avoid direct contact between the cathode and cathode, which would cause short circuits in the electrodes and affect the life of the electrodes. Non-conductive materials (plastic fibers) can enhance the mechanical stability of the electrodes, allowing them to maintain good performance during long-term operation.
[0023] The use of the material of the present invention in electrodes is one aspect of its scope of use.
[0024] The method of preparing electrodes can effectively avoid the high costs caused by ion recycling and material regeneration, thereby improving the applicability of the material.
[0025] Furthermore, the preparation method of the HPC anode and the HPC cathode comprises the following steps: S1: The layered porous adsorption material prepared above and the amine compound solution are mixed, heated and stirred, washed and dried to obtain cationic HPC powder; The layered porous adsorption material prepared above is mixed with an acid solution, heated and stirred, washed and dried to obtain anionic HPC powder; S2: dissolving the cationic HPC powder, carbon black and polytetrafluoroethylene prepared in step S1 in an ethanol solution, and continuously stirring under ultrasonic conditions to form cationic black micelles; The anionic HPC powder, carbon black and polytetrafluoroethylene prepared in step S1 are dissolved in an ethanol solution and continuously stirred under ultrasonic conditions to form anionic black micelles; S3: pressing the cationic black micelles prepared in step S2 onto a titanium mesh, and preparing an HPC anode after drying; The anionic black micelles prepared in step S2 are pressed onto a titanium mesh and dried to prepare an HPC cathode.
[0026] In the preparation of HPC anode and HPC cathode, polytetrafluoroethylene acts as a binder to help the material to be molded and form a hardened structure to ensure that the electrode material does not collapse under the subsequent hydraulic fluid impact. This addition amount is based on the addition amount in the general electrode manufacturing process in the prior art.
[0027] Further, the amine compound solution in step S1 includes one or more of an organosilicon quaternary ammonium salt solution, a polyhexamethyleneguanidine hydrochloride solution, and a polyethyleneimine solution; And / or, the heating temperature of the heating and stirring of the cationic HPC powder in step S1 is 70-90° C., the stirring speed of the heating and stirring is 90-110 r / min, and the heating and stirring time is 20-28h; And / or, in step S1, the drying temperature of the cationic HPC powder is 50-70° C., and the drying time is 5-7 hours.
[0028] Further, the acid solution in step S1 includes one or more of HNO3 solution, concentrated sulfuric acid solution, potassium permanganate solution, ammonium persulfate solution, and chlorosulfonic acid solution; And / or, the heating temperature of the heating and stirring of the anionic HPC powder in step S1 is 50-70° C., the stirring speed of the heating and stirring is 90-110 r / min, and the stirring time of the heating and stirring is 1-3 h; And / or, the drying temperature of the anionic HPC powder in step S1 is 100-120° C., and the drying time is 1-3 hours.
[0029] Furthermore, in step S2, the mass ratio of cationic HPC powder, carbon black and polytetrafluoroethylene is 7-9:1:1.
[0030] Furthermore, in step S3, the drying temperature of the cationic black micelles pressed on the titanium mesh is 70-85° C., and the drying time is 3-5 h; In step S3, the anionic black micelles are pressed on the titanium mesh and dried at a temperature of 70-85° C. for a drying time of 3-5 h.
[0031] In addition to the internal electric field brought by the HPC anode and HPC cathode's own electrical properties, there is also an external electric field brought by the external plate voltage. The combined effect of the two can make the adsorption effect stronger.
[0032] The regulation of the electric field is mainly through two aspects: (1) the internal electric field strength. The surface electrical properties of the material can be enhanced by the number density of the groups installed by the load, but it is not an unlimited superposition of groups, because too many groups will affect the specific surface area of the material, or agglomeration will occur, affecting the final adsorption effect. (2) The external electric field strength can improve the adsorption effect by increasing the external voltage, but if the external voltage is too high, other side reactions will occur, such as electrolysis of water, and even the formation of disinfection by-products, which is not economical and safe. Therefore, the optimal control range of the external voltage is 1.2V and below.
[0033] The electric adsorption device of the present invention can be directly added into sewage waste liquid to realize adsorption due to its own electrical property, and is particularly applicable to nitrate waste liquid.
[0034] This application can achieve highly selective adsorption of nitrate. Highly selective adsorption is achieved by regulating the material surface structure. In the basic material synthesis stage, a carbon matrix with rich and large voids is obtained by reacting silicon dioxide and polytetrafluoroethylene. Then, special functional groups such as organosilicon quaternary ammonium salt groups are installed (bonded) on the carbon matrix. The functional groups have advantages in adsorbing nitrates due to their special bonding force. The main adsorption mechanism is divided into three points: (1) Ion polarization Nitrate ions have certain polarizability due to their structural characteristics. When interacting with quaternary ammonium groups, they can deform to a certain extent, thus forming a tighter bond with the quaternary ammonium groups and enhancing the adsorption effect. However, the electron cloud distribution of chloride ions is relatively stable, and the polarizability is weak. The main interaction between them and quaternary ammonium groups is simple electrostatic interaction. The lack of this additional binding force generated by polarization leads to relatively weak adsorption capacity.
[0035] (2) Ion hydration Nitrate ions have a relatively weak binding force with water molecules in aqueous solution, and a relatively small hydration radius, making them more likely to approach and adsorb to quaternary ammonium groups. Chloride ions will strongly bind to water molecules in aqueous solution to form larger hydrated ions with a larger hydration radius. This layer of water molecule shell will, to a certain extent, hinder the direct contact between chloride ions and quaternary ammonium groups, thereby weakening the adsorption capacity of quaternary ammonium groups for chloride ions.
[0036] (3) Chemical stability and structural factors The nitrate ion has a relatively stable planar triangular structure. There is a certain electron delocalization phenomenon between the three oxygen atoms and the central nitrogen atom, which makes the chemical properties of the entire ion unique. This structure and chemical stability enable the nitrate ion to form a relatively stable adsorption complex with the quaternary ammonium group through various means (such as electrostatic interaction, hydrogen bonding, ion-π interaction, etc.) when interacting with the quaternary ammonium group. The chloride ion has a simple structure and relatively simple chemical properties. It mainly interacts with the quaternary ammonium group through electrostatic interaction. The stability of the adsorption complex formed is relatively poor, resulting in its adsorption capacity being inferior to that of the nitrate ion.
[0037] Compared with the prior art, the layered porous adsorption material, preparation method and electric adsorption device described in the present invention have the following advantages: 1. This application greatly improves the adsorption capacity and adsorption speed. This application uses the chemical etching effect produced by the reaction of silicon dioxide and polytetrafluoroethylene to form a layered porous structure on the surface of the material. The layered porous structure forms a smooth ion channel. The electrosorption technology effectively absorbs nitrate ions (NO3 ⁻ ) are adsorbed onto the electrode for efficient removal.
[0038] 2. The concentrated solution obtained in this application can be utilized as a resource. After the electrode is saturated with adsorption, desorption and regeneration can be achieved by simple short-circuiting or reverse power supply. The regenerated electrode can continue to be used, reducing the consumption and replacement frequency of electrode materials, and further reducing operating costs and energy consumption. The regenerated concentrated solution contains a high concentration of nutrients such as nitrate, which can be used as a raw material for the production of nitrogen fertilizer. After further processing, adding some necessary auxiliary ingredients and adjusting the formula, it can be made into a compound fertilizer or special fertilizer suitable for the needs of different crops, providing the required nitrogen elements for the growth of crops, promoting the growth and development of crops, and improving the yield and quality of crops.
[0039] 3. The present application can achieve highly selective adsorption of nitrate. Through specific electrode material design and electric field regulation, the target ions can be accurately identified and adsorbed, while having little interference with other ions or impurities in the waste liquid. For example, in complex industrial wastewater containing multiple ions, nitrate can be effectively separated from numerous ions, improving the pertinence and efficiency of treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings: Figure 1A diagram of the HPC material described in Example 1 of the present invention (A is an electron microscopic photograph of the adsorption material under a low magnification microscope, B is an electron microscopic photograph of the adsorption material under a high magnification microscope; C is an electron microscopic photograph of an anionic HPC material under a low magnification microscope, D is an electron microscopic photograph of an anionic HPC material under a low magnification microscope; E is an electron microscopic photograph of a cationic HPC material under a low magnification microscope, and F is an electron microscopic photograph of a cationic HPC material under a high magnification microscope); Figure 2 The selectivity difference diagram of the electrodes at different voltages and different concentrations described in Example 1 of the present invention (A is the selectivity difference of the electrodes at different voltages for NO3 - and Cl - The ion removal capacity of NO3 at different voltages. - :Cl - Selectivity; B is NO3 at different feed concentration ratios - and Cl - The ion removal capacity of D is NO3 at different feed concentration ratios. - :Cl - selectivity); Figure 3 This is a schematic diagram of the adsorption capacity and adsorption selectivity described in Example 1 of the present invention; Figure 4 This is a schematic diagram of the structure of the electric adsorption device described in Example 2 of the present invention.
[0041] Description of reference numerals: 1. Constant voltage power supply; 2. Water inlet tank; 3. Peristaltic pump; 4. Water outlet tank; 5. Flow meter. DETAILED DESCRIPTION
[0042] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.
[0043] Example 1 ① 2g chitosan ((C6H 11 NO4) n ) was dissolved in 100 mL of glacial acetic acid (5 wt%) and stirred for 12 h until the solid was completely dissolved to form a light yellow gel-like liquid (chitosan solution). Then 4 mL of colloidal SiO2 (SiO2, 30 wt%) was added to the chitosan solution and stirred for 12 h to form a transparent gel-like solution (chitosan / SiO2 solution). Subsequently, 4 mL of polytetrafluoroethylene (PTFE, 60 wt%) was added to the chitosan / SiO2 solution and stirred for 12 h to form a milky white solution (chitosan / SiO 2 / PTFE solution). Finally, the chitosan / SiO2 / PTFE solution was placed in a freeze drying oven for 48 hours. The dried solid mixture (chitosan / SiO2 / PTFE solid) was heated to 900°C at a heating rate of 10°C / min at room temperature in a N2 atmosphere, and then maintained at 900°C for 4 hours. After cooling, the porous carbon powder was washed several times with deionized water to remove impurities and dried at 100°C for 2 hours. The adsorbent material (chitosan-based hierarchical porous carbon HPC) was obtained, and the electron microscope image is shown in FIG. Figure 1 As shown in A and B.
[0044] ② Add 1.5g HPC powder and 5mL organosilicon quaternary ammonium salt solution (SQAS, SiO3C 26 H 58 N + Cl - , 40wt% methanol solution) and 35mL deionized water. The beaker was placed in a water bath at 80°C and stirred continuously at a speed of 100 r / min. After 24h of hydrothermal reaction, the obtained product was washed several times with anhydrous ethanol and deionized water until there was no obvious foamy substance. The quaternized carbon was dried at 60°C for 6h. The HPC loaded with quaternary ammonium functional groups was named cationic HPC. The electron microscopy image is shown in Figure 1 As shown in E and F.
[0045] ③ Add 5 g of HPC powder to 40 mL of HNO3 solution (mixed with deionized water in a ratio of 1:1), and heat the mixture at 60 °C and stir at 100 r / min for 2 h. After cooling, wash the solid several times with deionized water until the pH value is about 7.0. Finally, the carboxylated carbon is dried at 110 °C for 2 h and named anionic HPC. The electron microscope image is shown in the figure. Figure 1 As shown in C and D.
[0046] ④ The electrode was prepared by roller pressing. The anode preparation method is as follows. Cationic HPC powder, carbon black and polytetrafluoroethylene were mixed in an ethanol solution in a ratio of 8:1:1 and stirred continuously under ultrasonic conditions until black micelles were formed. The black micelles were then pressed onto a titanium mesh and dried at 80°C for 4h. The anode was named HPC anode. The preparation method of the cathode was the same as that of the anode, except that the cationic HPC was replaced by anionic HPC. The cathode was named HPC cathode. The size of each electrode is 5cm×5cm (25cm 2 ), with a mass of approximately 150 mg.
[0047] During the experiment, the HPC anode and the HPC cathode are placed symmetrically with a spacing of 5 mm, and can be filled with plastic fibers. Wires are led out from the electrodes respectively, and the wires are connected to the positive and negative electrodes of the power supply respectively to obtain an electric adsorption device.
[0048] like Figure 2 As shown, in 10 / 10 mM NaCl / NaNO3 solution, the adsorption capacity of the electrode at 0, 0.4, 0.8, and 1.2 V voltages ( Figure 2 A) and selectivity ( Figure 2 C); At 1.2 V voltage, the adsorption capacity when the initial NaCl / NaNO3 concentration ratios were 10 / 2.5 mM, 10 / 5 mM, and 10 / 10 mM ( Figure 2 B) and selectivity ( Figure 2 D) Under the influence of the electric field of the cathode and anode, the differently charged ions in the solution move to the oppositely charged electrode plates and are stored in the pores of the electrode material, such as NH4 in high-concentration wastewater. + and NO3 - , NH4 + Will be adsorbed to the cathode by the electric field, NO3 - It will be adsorbed to the anode by the electric field. HPC material has a macroporous-mesoporous multilayer structure, which can achieve rapid ion storage and transport; in addition, because HPC has been modified, its material surface is loaded with positive and negative ion charges, which can enhance the electric field efficiency and can spontaneously and selectively adsorb NH4 even without electricity. + and NO3 - 。 The adsorption rate is 5~6 times higher than that of traditional activated carbon-based materials, and the adsorption capacity is 2~3 times higher.
[0049] like Figure 3 As shown in the figure, in 10 / 10 mM NaCl / NaNO3 solution, the adsorption capacity, adsorption rate and selectivity of the experimental group (HPC cathode and cathode) and the control group (ordinary commercial activated carbon) electrodes at a voltage of 1.2 V. The adsorption capacity of the experimental group for chloride ions and nitrate ions was 41 mg / g, which was 80% higher than that of the control group (ordinary commercial activated carbon), and the adsorption rate was 2 mg / g / min, which was 150% higher than that of the control group (ordinary commercial activated carbon). The selectivity of the experimental group for nitrate was 2.8, while that of the control group was only 1.0.
[0050] Example 2 like Figure 4 As shown, the HPC anode and the HPC cathode prepared in Example 1 are placed symmetrically with a spacing of 5 mm, and can be filled with plastic fibers. Wires are led out from the electrodes respectively, and the wires are connected to the positive and negative electrodes of the constant voltage power supply 1 respectively to obtain an electric adsorption device.
[0051] The liquid in the water inlet tank 2 flows into the gap between the electric adsorption plates of the electric adsorption device through the peristaltic pump 3. Under the action of the electric field force, the ions are adsorbed, the solution is purified and flows out, and after passing through the flow meter 5, it enters the water outlet tank 4. After the adsorption is saturated, the voltage needs to be reversed to desorb the adsorbed ions on the electrode.
[0052] The wastewater concentration used in the experiment was 200-800 mg / L nitrate. The higher the nitrate concentration, the stronger the effect. The process of the present invention can treat nitrate wastewater with a maximum concentration of 1000 mg / L, which is high-concentration wastewater. The traditional method for treating nitrate wastewater is mostly denitrification, and its treatment concentration is below 200 mg / L. High-concentration nitrate wastewater often appears in the catalyst material production industry, steel processing mixed acid wastewater, electroplating wastewater, pickled food production wastewater or fermentation wastewater.
[0053] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a layered porous adsorption material, characterized in that: The method comprises the following steps: firstly mixing chitosan solution and SiO2, then adding polytetrafluoroethylene and stirring to form a milky white solution; The milky white solution is freeze-dried to obtain a solid mixture, the solid mixture is heat-treated in an inert gas, cooled, washed with deionized water, and dried to obtain a layered porous adsorption material.
2. The method for preparing a hierarchical porous adsorption material according to claim 1, characterized in that: The solvent in the chitosan solution was glacial acetic acid; The mass ratio of chitosan solution, SiO2, and polytetrafluoroethylene is 1:4:2-4; And / or, SiO2 is colloidal SiO2.
3. The method for preparing a hierarchical porous adsorption material according to claim 1, characterized in that: The inert gas is nitrogen; And / or, the heat treatment temperature is 890-910°C and the heating rate is 8-12°C / min; And / or, the heat treatment time is 3-5h; And / or, the drying temperature is 90-110°C, and the drying time is 1.8-2.2h.
4. A layered porous adsorption material prepared by the method for preparing a layered porous adsorption material according to any one of claims 1 to 3.
5. An electric adsorption device, characterized in that: A HPC anode and a HPC cathode prepared using the hierarchical porous adsorption material of claim 4; The HPC anode and the HPC cathode are placed symmetrically, the interval between the HPC anode and the HPC cathode is 4-6 mm, plastic fibers are filled between the HPC anode and the HPC cathode, wires are led out from the HPC anode and the HPC cathode respectively, and the HPC anode and the HPC cathode are connected to the positive and negative electrodes of the power supply respectively through the wires to obtain an electric adsorption device; And / or, the voltage of the electric adsorption device connected to the power supply is less than 1.2V.
6. The electric adsorption device according to claim 5, characterized in that: The preparation method of the HPC anode and the HPC cathode comprises the following steps: S1: mixing a layered porous adsorption material prepared according to claim 4 and an amine compound solution, heating and stirring, washing and drying to obtain a cationic HPC powder; The layered porous adsorption material prepared in claim 4 and the acid solution are mixed, heated and stirred, washed and dried to obtain anionic HPC powder; S2: dissolving the cationic HPC powder, carbon black and polytetrafluoroethylene prepared in step S1 in an ethanol solution, and continuously stirring under ultrasonic conditions to form cationic black micelles; The anionic HPC powder, carbon black and polytetrafluoroethylene prepared in step S1 are dissolved in an ethanol solution and continuously stirred under ultrasonic conditions to form anionic black micelles; S3: pressing the cationic black micelles prepared in step S2 onto a titanium mesh, and preparing an HPC anode after drying; The anionic black micelles prepared in step S2 are pressed onto a titanium mesh and dried to prepare an HPC cathode.
7. The electric adsorption device according to claim 6, characterized in that: The amine compound solution in step S1 includes one or more of an organosilicon quaternary ammonium salt solution, a polyhexamethyleneguanidine hydrochloride solution, and a polyethyleneimine solution; And / or, the heating temperature of the heating and stirring of the cationic HPC powder in step S1 is 70-90° C., the stirring speed of the heating and stirring is 90-110 r / min, and the heating and stirring time is 20-28h; And / or, in step S1, the drying temperature of the cationic HPC powder is 50-70° C., and the drying time is 5-7 hours.
8. The electric adsorption device according to claim 6, characterized in that: The acid solution in step S1 includes one or more of HNO3 solution, concentrated sulfuric acid solution, potassium permanganate solution, ammonium persulfate solution, and chlorosulfonic acid solution; And / or, the heating temperature of the heating and stirring of the anionic HPC powder in step S1 is 50-70° C., the stirring speed of the heating and stirring is 90-110 r / min, and the stirring time of the heating and stirring is 1-3 h; And / or, the drying temperature of the anionic HPC powder in step S1 is 100-120° C., and the drying time is 1-3 hours.
9. The electric adsorption device according to claim 6, characterized in that: In step S2, the mass ratio of cationic HPC powder, carbon black and polytetrafluoroethylene is 7-9:1:
1.
10. The electric adsorption device according to claim 6, characterized in that: In step S3, the drying temperature of the cationic black micelles pressed on the titanium mesh is 70-85° C., and the drying time is 3-5 h; In step S3, the anionic black micelles are pressed on the titanium mesh and dried at a temperature of 70-85° C. for a drying time of 3-5 h.
Citation Information
Patent Citations
Preparation method of magnetic chitosan and method for adsorbing tannic acid in water
CN104014316A
Porous carbon electrode based on high-temperature pyrolysis of chitosan, and preparation method of porous carbon electrode
CN110033957A
Preparation of manganese ferrite / porous graphite phase carbon nitride and method for treating low-concentration uranium-containing wastewater
CN111054297A
Preparation and application of nitrate selective extended voltage capacitive deionization electrode
CN113213599A